PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KESELAMATAN DAN KESEHATAN KERJA TERHADAP KEPUASANKERJA KARYAWAN BAGIAN PRODUKSI PADA PT. TIRTA INVESTAMA MAMBAL DI KABUPATEN BADUNG - I Dewa Gede Punarbawa; I Wayan Widnyana; I Gusti Ngurah Bagus Gunadi (VALUES, 2022)
Employee job satisfaction is a very important thing in the organization's efforts to achieve its goals, so it is important to pay attention to the factors that determine employee job satisfaction. Transformational leadership, occupational safety and health are independent variables that can affect employee job satisfaction. The purpose of this study was to determine the effect of transformational leadership, occupational safety and health on employee job satisfaction at PT. Tirta Investama Mambal in Badung Regency. This research was conducted at PT. Tirta Investama Mambal, having his address at Banjar Gumasih, Mambal Village, Abiansemal District, Badung Regency. The object of this research is transformational leadership, occupational safety and health and employee job satisfaction. The population in this study were employees of the production department at PT. Tirta Investama Mambal in Badung Regency in 2020 as many as 89 employees. Determination of the sample in this study using the saturated sample or census method is a sampling technique when all members of the population are used as samples. The number of samples as many as 89 employees of the production division of PT. Tirta Investama Mambal in Badung Regency, Data analysis using multiple linear regression. The result of the research is that transformational leadership has a positive and significant effect on employee job satisfaction at PT. Tirta Investama Mambal in Badung Regency. Work safety has a positive and significant effect on employee job satisfaction at PT. Tirta Investama Mambal in Badung Regency. Occupational health has a positive and significant effect on employee job satisfaction at PT. Tirta Investama Mambal in Badung Regency.